Congenital insensitivity to pain with anhidrosis - Ayyazuddin, Meher; Maqsood, Nushra; Khan, Saman; Muhammad Ali; Kakalia, Spenta (Journal of the Pakistan Medical Association, 2025)
Congenital Insensitivity to Pain with Anhidrosis (CIPA) is characterised by disruption of sensory neurons caused by genetic mutations in the Neurotrophic Tyrosine Kinase 1 (NTRK1) gene which leads to impaired pain sensation, accompanied by anhidrosis (the inability to sweat) and varying degrees of intellectual disability. Herein, we report a case of CIPA that presented with infection of an amputated left toe, with prior admissions due to various injuries. The patient had no apparent intellectual disability. A general physical examination yielded various scars with a predilection for the elbows, knees, and shins as well as an early loss of teeth (front incisors of the lower jaw). The patient exhibited anhidrosis, a self-injurious behaviour, and an abnormal response to painful stimuli, all of which led to a clinical diagnosis of CIPA. Keywords: Congenital insensitivity to pain with anhidrosis, Loss of teeth, High body temperature.